2015
DOI: 10.5194/acp-15-3497-2015
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol processing and CCN formation of an intense Saharan dust plume during the EUCAARI 2008 campaign

Abstract: Abstract. Atmospheric processing and CCN formation of Saharan dust is illustrated through the analysis of a case of dust transport over northern Europe. This spread of dust is investigated by combining satellite, airborne and ground-based observations and the non-hydrostatic mesoscale model Meso-NH. The altitude of the dust plume during its transport to northwestern Europe was assessed using the CALIPSO observations and our model results. The major dust plume was transported toward Mediterranean and European r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 128 publications
1
36
0
Order By: Relevance
“…With increasing maximum diameter (D max ), the ice crystals become more complex and their effective density decreases (Heymsfield et al, 2010). The DARDAR algorithm describes this relationship using a combination of in situ measurements by Brown and Francis (1995) for lowdensity aggregates (D max > 300 µm) and by Mitchell (1996) for hexagonal columns (D max < 300 µm). We derive the n ice (DARDAR-Nice) following the approach presented by Sourdeval et al (2018) on the DARDAR-Cloud parameters of the ice water content (IWC) and the normalization factor of the modified gamma size distribution (N * 0 ).…”
Section: Spaceborne Cloud Observationsmentioning
confidence: 99%
“…With increasing maximum diameter (D max ), the ice crystals become more complex and their effective density decreases (Heymsfield et al, 2010). The DARDAR algorithm describes this relationship using a combination of in situ measurements by Brown and Francis (1995) for lowdensity aggregates (D max > 300 µm) and by Mitchell (1996) for hexagonal columns (D max < 300 µm). We derive the n ice (DARDAR-Nice) following the approach presented by Sourdeval et al (2018) on the DARDAR-Cloud parameters of the ice water content (IWC) and the normalization factor of the modified gamma size distribution (N * 0 ).…”
Section: Spaceborne Cloud Observationsmentioning
confidence: 99%
“…The days from 17 to 20 May are referred as "scavenged background situation" (Mensah et al, 2012), because they are dominated by a northerly wind from the North Sea associated with a low aerosol mass loading, due to wet scavenging. The period starting from 23 May is dominated by long-range transport of dust from Sahara desert (Roelofs et al, 2010;Bègue et al, 2015).…”
Section: Measurementsmentioning
confidence: 99%
“…OM prediction is also affected by meteorological errors. Bei et al (2012) found that the uncertainties in meteorological initial conditions have a significant impact on the simulations of the peaks, horizontal distribution, and temporal variation of SOA. The same authors demonstrated that the spread of the simulated peaks can reach up to 4.0 µg m −3 .…”
Section: Aloft Aerosol Mass Concentrationmentioning
confidence: 99%
“…During its long-range transport the SAL affects the Earth's radiation budget in two different ways. First, mineral dust aerosols may act as ice-nucleating particles (INPs) or cloud condensation nuclei (CCN -only when being internally mixed with soluble material) in water and ice clouds, hence influencing cloud microphysics -this effect is referred to as "indirect" mineral dust aerosol effect (Twomey, 1974(Twomey, , 1977Karydis et al, 2011;Bègue et al, 2015;DeMott et al, 2015;Boose et al, 2016). Thus, cloud formation, lifetime and occurrence as well as precipitation and ice formation may be manipulated by Saharan dust deposition into the cloud layer (Mahowald and Kiehl, 2003;Seifert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%